Occurrence of the lessepsian species Portunus pelagicus (Crustacea) and Apogon pharaonis (Pisces) in the marine area of Rhodes Island - CORSINI-FOKA, M.; KONDILATOS, G.; ECONOMIDIS, P.S. (Mediterranean Marine Science, 2004)
A large number of Red Sea species are colonizing the eastern Mediterranean Sea via the Suez Canal, mainly following the Anatolian coasts and spreading westwards. Portunus pelagicus is one of the most common Red Sea swimming crabs, first recorded in the Levantine Basin in 1898. Four specimens of P. pelagicus were collected in different marine areas of Rhodes Island from 1991 to 2000, while three specimens of the lessepsian fish Apogon pharaonis, first recorded in the Mediterranean in 1947, were caught during 2002 in the NW coast of Rhodes. The sub-tropical character of the marine area around Rhodes seems to facilitate the propagation of lessepsian species. These migrants have reached the island at different velocity and degree of establishment of their populations. The occurrence of the blue swimmer crab P. pelagicus and of the bullseye cardinal fish A. pharaonis increases the number of the decapod Crustacea and fish species of Red Sea origin observed in Greek waters.